2019
DOI: 10.3390/rs11060687
|View full text |Cite
|
Sign up to set email alerts
|

Large Anomalies in the Tropical Upper Troposphere Lower Stratosphere (UTLS) Trace Gases Observed during the Extreme 2015–16 El Niño Event by Using Satellite Measurements

Abstract: It is well reported that the 2015–16 El Niño event is one of the most intense and long lasting events in the 21st century. The quantified changes in the trace gases (Ozone (O3), Carbon Monoxide (CO) and Water Vapour (WV)) in the tropical upper troposphere and lower stratosphere (UTLS) region are delineated using Aura Microwave Limb Sounder (MLS) and Atmosphere Infrared Radio Sounder (AIRS) satellite observations from June to December 2015. Prior to reaching its peak intensity of El Niño 2015–16, large anomalie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The most recent ENSO, which was developed in 2014 and strengthened in the summer, has caused global impacts [61]. In Ethiopia, the dry kiremt seasons are closely linked to the significantly warmer Pacific sea surface temperatures [39].…”
Section: Resultsmentioning
confidence: 99%
“…The most recent ENSO, which was developed in 2014 and strengthened in the summer, has caused global impacts [61]. In Ethiopia, the dry kiremt seasons are closely linked to the significantly warmer Pacific sea surface temperatures [39].…”
Section: Resultsmentioning
confidence: 99%
“…They demonstrated the importance of the large-scale atmospheric dynamics and the stratospheric intrusions for high O 3 and low WV over Lhasa within the ASMA by using in situ balloon-borne measurements. The O 3 and WV changes strongly influence the background temperature structure within the UTLS region (Venkat Ratnam et al, 2016;Ravindra Babu et al, 2019b). Further, we investigated the tropopause temperature changes within the ASMA by using COSMIC RO data.…”
Section: Trace Gases Anomalies Observed Within the Asma In 2015mentioning
confidence: 99%
“…It is well known that the tropopause plays a crucial role in the exchange of WV, O 3 , and other chemical species between the troposphere and the stratosphere. Most of these exchanges (WV to the lower stratosphere and O 3 to the upper troposphere) known as stratosphere-troposphere exchange (STE) take place around the tropopause region (Fueglistaler et al, 2009;Venkat Ratnam et al, 2016;Ravindra Babu et al, 2019b). It is well reported that the tropopause within the ASMA is higher than the outside regions at the same latitude (Randel et al, 2010;Santee et al, 2017).…”
Section: Tropopause Temperature Anomalies In 2015mentioning
confidence: 99%
“…The uplifting of boundary layer pollutants to the tropopause level occurs primarily on the eastern side of the anticyclone, centered near the southern flank of the Tibetan Plateau, north-eastern India, Nepal, and north of the Bay of Bengal. However, a more detailed and a higher quality of dataset is needed to further understand the effects of the Tibetan Plateau on the transport of different tracers and pollutants to the UTLS region (Ravindrababu et al, 2019…”
Section: Variability Of the Anticyclonementioning
confidence: 99%